Validity of Jones criteria for diagnosis of rheumatic fever and rheumatic heart disease - Rana, Mukesh; Kumar, Brijesh (International Journal of Advances in Medicine, 2017)
Background: Acute rheumatic fever (ARF) remains one of the major causes of cardiovascular disease burden throughout the world particularly among the young. Availability of echocardiography / Doppler adds a different angle to the diagnosis of ARF and RHD in India. Methods: The present one year cross-sectional study was conducted on patients of rheumatic fever (RF) and rheumatic heart disease (RHD) of age group of 5-15 years from in and around Kanpur, India to test the validity of Jones criteria. Results: Out of 950 patients, majority had arthralgia (85%) and fever (82%). Nearly 23% had arthritis, 67% patients had an increased PR interval in ECG and increased ASO titre was seen in 93% of patients. Only1% was having subcutaneous nodules, 2% had Erythema marginatum and no patient had chorea while 24 % had a positive throat swab culture. Conclusions: Jones criteria can be made more simple and easy to apply. The two diagnostic features of RF and RHD were arthritis/arthralgia and carditis. The other major as well as minor criteria had no importance for diagnosis of new cases.